INFLUENCE OF CELEBRITY ENDORSER ON PURCHASING DECISIONS FOR SLIMMING PRODUCTS (CASE STUDY ON USERS OF WRP PRODUCTS IN KARAWANG) - Reza Pahlevi (Fakultas Ekonomi dan Bisnis, 2019)
Penelitian yang berjudul